Implementasi Metode Drill and Pratice untuk Meningatkan Pemahaman Siswa dalam Pelajaran PAI di Kelas X SMKS Budi Agung - Arif Mukti Habibi; Nurman Ginting (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study aims to examine the implementation of the Drill and Practice method in improving students' understanding of Islamic Religious Education in class X of SMKS Budi Agung. The Drill and Practice method is a learning approach that emphasizes repetitive practice with the aim of improving students' skills and understanding effectively. This study uses the observation stage and data analysis using quantitative analysis. The results of the study show that students' learning outcomes have increased in each cycle, in cycle I the average score was 69.2 with a completion percentage of 52%, while in cycle II the average score was 83.4 with a completion percentage of 92%. The increase in student learning outcomes between cycle I and cycle II showed an increase of 40%. So it can be concluded that the application of the Drill and Practice method to class X students at SMKS Budi Agung can improve student learning outcomes in Islamic Religious Education subjects with the material Achieving Success with Competence in Good Work Ethics (QS. Al-Maidah: 48 and QS. At-Taubah: 105).